Correlation between renal histopathology and renal ultrasound in dogs. (April 2020) - Burti, Silvia; Zotti, Alessandro; Bonsembiante, Federico; Mastellaro, Giorgia; Banzato, Tommaso
Abstract: Fifty-three privately owned dogs were included in the study. Ultrasonography of the kidneys was performed ante mortem . All the dogs died or were euthanized for reasons unrelated to this study. Histopathology of both kidneys was performed, and a degeneration and an inflammation score ranging from zero to two was assigned by consensus between two pathologists. A numerical score based on a three level semi-quantitative scale (0, 0.5, 1) was assigned by consensus between two of the authors to the following ultrasonographic abnormalities: cortico-medullary definition, echogenicity of the renal cortex, echogenicity of the medulla, renal shape, cysts, scars, mineralizations, subcapsular perirenal fluid accumulation, pyelectasia. The scores deriving from the consensus were summed to create a summary index called renal ultrasound score (RUS). Statistically significant differences in cortico-medullary definition, echogenicity of the renal cortex, echogenicity of the medulla, renal shape, scars and pyelectasia were evident between the degeneration score groups. There were significantly different distributions of cortico-medullary definition, renal shape and scars between the inflammatory score groups. There were statistically significant differences in the RUS between the degenerative score groups (F = 24.154, p -value<.001). Post-hoc tests revealed significant differences between all groups. There were no significant differences in the RUS between the inflammatory score groups (F = 1.312, p -value = .264). Post-hoc tests revealed no significant differences between groups. The results of the present study suggest that the number and severity of the ultrasonographic abnormalities are correlated with the severity of the kidney degeneration. On the other hand, inflammation showed poor influence on the ultrasonographic appearance of the kidneys. Highlights: The relationship between renal ultrasonography and renal pathology was evaluated. Degeneration has as a significant influence on ultrasonography of the kidneys. Inflammation has a poor influence on ultrasonography of the kidneys.